2005
DOI: 10.1111/j.0021-8782.2005.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic anatomy of the sural nerve in the postnatal developing rat: a longitudinal and lateral symmetry study

Abstract: Rat sural nerve is widely used in experimental studies investigating injury and regeneration of the peripheral nervous system. However, it has not yet been established whether morphological and morphometric parameters differ within corresponding levels of the rat sural nerve. The aims of the present study were to investigate the normal morphological and morphometric aspects of the sural nerve in postnatal developing female rats, with special attention to longitudinal morphology and lateral symmetry. Rats aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
78
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 24 publications
17
78
0
7
Order By: Relevance
“…Nevertheless, the distributions in the proximal segments of the radial nerves, the distal segments of the ulnar and median nerves, and the lateral proper digital nerve of the third finger tended to be bimodal in animals 7 weeks old. This observation agrees with that of Jeronimo et al (2005), who showed, for rat sural nerves, unimodal distribution in young animals (30 days), a tendency for bimodal distribution in some segments of animals 3 months old, and a well-established bimodal distribution in animals 6 months old. Further studies on the brachial plexus nerves are needed to establish fiber and axon diameter distributions for adult rats.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Nevertheless, the distributions in the proximal segments of the radial nerves, the distal segments of the ulnar and median nerves, and the lateral proper digital nerve of the third finger tended to be bimodal in animals 7 weeks old. This observation agrees with that of Jeronimo et al (2005), who showed, for rat sural nerves, unimodal distribution in young animals (30 days), a tendency for bimodal distribution in some segments of animals 3 months old, and a well-established bimodal distribution in animals 6 months old. Further studies on the brachial plexus nerves are needed to establish fiber and axon diameter distributions for adult rats.…”
Section: Discussionsupporting
confidence: 93%
“…The following increases in nerve parameters accompanying age are corroberated by our findings: rat nerve area (Hashizume and Kanda, 1995;Jeronimo et al, 2005), myelinated fiber diameter in rats and man (Gutrecht and Dyck, 1970;Jacobs and Love, 1985;Ouvrier et al, 1987;Schellens et al, 1993;Fazan and Lachat, 1997;Jeronimo et al, 2005), axonal diameter in rats (Hashizume and Kanda, 1995), and myelin sheath area in man (Thomas and Ochoa, 1984;Jacobs and Love, 1985;Schröder et al, 1988). The present study is the first to document such differences over the short interval of 3 weeks: between the ages of 4 and 7 weeks, which is indicative of the intense maturation of the peripheral nervous system during this life period in the rat.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In the more distal areas of the foot, the sural nerve is responsible for the sensory innervation of the lateral side and dorsal central area (Cobianchi et al, 2014) but it also contains a small percentage (4%) of motor fibers (Swett et al). The extensive use of the sural nerve in experimental investigations about degeneration and regeneration following nerve injury is described mainly from male rats (Unger et al, 1998) while the sural nerves from female rats was less investigated (Jeronimo et al, 2005(Jeronimo et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%